2016
DOI: 10.1002/anie.201511457
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Strained γ‐Lactams by Palladium(0)‐Catalyzed C(sp3)−H Alkenylation and Application to Alkaloid Synthesis

Abstract: A variety of strained α-alkylidene-γ-lactams were synthesized by palladium(0)-catalyzed intramolecular C(sp(3) )-H alkenylation from easily accessible acyclic and monocyclic bromoalkene precursors. These lactams are valuable intermediates for accessing various classes of mono- and bicylic alkaloids containing a pyrrolidine ring, as illustrated with the synthesis of an advanced model of the marine natural product plakoridine A and of the indolizidine alkaloid δ-coniceine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 67 publications
1
41
0
1
Order By: Relevance
“…[21] In asubsequent report, Baudoin and co-workers further demonstrated that a-bromoacrylamide 37 is also ac ompetent substrate in this reaction and showed that monocyclic pyrrolidine derivatives can be obtained from acyclicp recusors. [22] Them echanism of these transformations is believed to be the same as in the case of aryl halides. In all the examples discussed previously,the putative arylpalladium(II) intermediates prior to the activation of C(sp 3 ) À Hbonds are generated from aryl or vinyl halides.Incontrast, LiØgault and Fagnou showed that C(sp 2 ) À Ha ctivation of pivaloylpyrrole 39 can generate the aryl-palladium species D1,w hich can undergo C(sp 3 )ÀHa ctivation to form sixmembered palladacycle D2 (Scheme 8).…”
Section: Aryl/vinyl Halidesmentioning
confidence: 98%
“…[21] In asubsequent report, Baudoin and co-workers further demonstrated that a-bromoacrylamide 37 is also ac ompetent substrate in this reaction and showed that monocyclic pyrrolidine derivatives can be obtained from acyclicp recusors. [22] Them echanism of these transformations is believed to be the same as in the case of aryl halides. In all the examples discussed previously,the putative arylpalladium(II) intermediates prior to the activation of C(sp 3 ) À Hbonds are generated from aryl or vinyl halides.Incontrast, LiØgault and Fagnou showed that C(sp 2 ) À Ha ctivation of pivaloylpyrrole 39 can generate the aryl-palladium species D1,w hich can undergo C(sp 3 )ÀHa ctivation to form sixmembered palladacycle D2 (Scheme 8).…”
Section: Aryl/vinyl Halidesmentioning
confidence: 98%
“…Related studies on desymmetrization of α-dialkyl groups via C–H activation from other laboratories have been limited to intramolecular Pd(0)-catalyzed C–H arylations (1422). An inspiring formal enantioselective intermolecular β-arylation of isobutyric esters has been demonstrated with moderate enantioselectivity (67:33 to 77:23 er) (23).…”
mentioning
confidence: 99%
“…[21] In einem späteren Bericht demonstrierten die Autoren außerdem, dass auch das a-Bromacrylamid 37 ein geeignetes Substrat in diesen Reaktionen ist und dass aus acyclischen Vorstufen monocyclische Pyrrolidinderivate erhalten werden kçnnen. [22] Es wird angenommen, dass der Mechanismus dieser Umwandlungen der gleiche wie bei den Arylhalogeniden ist. In allen zuvor erçrterten Beispielen werden die mutmaßlichen Arylpalladium(II)-Intermediate vor der Aktivierung der C(sp 3 )-H-Bindungen aus Aryl-oder Vinylhalogeniden gebildet.…”
Section: Frühe Arbeitenunclassified